USE OF ONLINE LEARNING MEDIA TO SUPPORT DIGITAL NEEDS - Frezy Paputungan (Jurnal Ilmu Pendidikan dan Budaya, 2021)
In today's developments, traditional learning activities are rarely found, school classrooms are emptied and replaced with digital classrooms that are presented virtually. Parents also play the role of homeroom teacher and suddenly have to help their children with their studies. The digital education ecosystem in Indonesia has a wide range of control spaces, including geographical differences, gaps in infrastructure distribution, gaps in educators' digital capabilities, and gaps in different teaching methods. Thus, several scenarios or strategies must be used to be used during the post-Covid 19 digital education transformation. The demand for using technology for learning has actually been around for a long time. Technological progress is unrelenting, unnoticed, and unavoidable, even unstoppable, but there are some application gaps. Among them are the availability of electricity, the availability of the internet, laptops, cellphones, television and geographical inequality where Indonesia faces various obstacles in deploying this infrastructure. A communication network must also be used. Teachers' competency levels are also inconsistent in their use of ICT, staffing gaps range from a lack of communication channels to acquire digital learning information to an equally important factor, support in ICT use. As for the reason, educators and teachers use digital technology, teachers become more confident by always accompanying the implementation of the application of digital technology in learning as an affirmative step in the introduction of learning technology innovations. To address digital needs in the learning process in schools, online learning media are needed that are easy to use and can support the achievement of student learning outcomes. Online learning media in the form of the Academia Edu application is believed to be able to solve student problems to facilitate the learning process anytime and anywhere. Apart from being easy to use, Academia Edu provides several online features including uploading/downloading pdf, complete document options, unlimited data sources, discussion options and much more